2013
DOI: 10.33549/physiolres.932614
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of captopril, olmesartan, melatonin and compound 21 on doxorubicin-induced nephrotoxicity in rats

Abstract: Chronic kidney disease (CKD) represents a serious public health problem with increasing prevalence and novel approaches to renal protection are continuously under investigation. The aim of this study was to compare the effect of melatonin and angiotensin II type 2 receptor agonist compound 21 (C21) to angiotensin converting enzyme inhibitor captopril and angiotensin II type 1 receptor blocker olmesartan on animal model of doxorubicin nephrotoxicity. Six groups of 3-month-old maleWistar rats (12 per group) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Previous research showed that use of melatonin significantly reduces drug-induced nephrotoxicity caused by oxidative stress. Such a mechanism was described for amikacin (Parlakpinar et al, 2003), vancomycin (Celik et al, 2005), gentamicin (Ozbek et al, 2005), methotrexate (Abraham et al, 2010), AmB (Lin and Chuang, 2010), and doxorubicin (Hrenák et al, 2013). At physiological concentrations (1 to 100 mM) melatonin affected the expression of genes involved in oxidative stress in cells treated with AmB (Lin and Chuang, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Previous research showed that use of melatonin significantly reduces drug-induced nephrotoxicity caused by oxidative stress. Such a mechanism was described for amikacin (Parlakpinar et al, 2003), vancomycin (Celik et al, 2005), gentamicin (Ozbek et al, 2005), methotrexate (Abraham et al, 2010), AmB (Lin and Chuang, 2010), and doxorubicin (Hrenák et al, 2013). At physiological concentrations (1 to 100 mM) melatonin affected the expression of genes involved in oxidative stress in cells treated with AmB (Lin and Chuang, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Rabbits were purchased from the animal house of King Fahd Medical Research Centre (KFMRC), King Abdulaziz University, KSA. Rabbits were maintained for Care and Use of Laboratory Animals according to the criteria of US National Institutes of Health (NIH Publication No 8523, revised 1985) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intraperitoneal cefotaxime was given for 5 days at the dose of 200 mg/kg once a day, starting 72 hours after surgery. Captopril dose in rats ranged from 10 to 100 mg in similar studies and the dose of 50 mg/kg/day was used in this study (15)(16)(17). Ketotifen was used in the dose of 1 mg/kg/day by orogastric lavage (18,19).…”
Section: Effects Of Captopril and Ketotifen On Protecting Against Renal Scarring Due To Pyelonephritis Injurymentioning
confidence: 99%